Landscape and Interaction. The Troodos Archaeological and Environmental Survey Project, Cyprus. Volume 2. The TAESP Landscape - Given, Michael (Council for British Research in the Levant, 2013)
The TAESP Landscape, the second of two volumes, presents an area-by-area analysis of the fieldwork and research undertaken by the Troodos Archaeological and Environmental Survey Project (TAESP) in the Troodos Mountains of Cyprus. Covering four regions of the survey area (The Plains, Karkotis Valley, Upper Lagoudhera Valley and The Mountains) the volume focuses on explicit research questions appropriate to each region. Organised geographically, chronologically and thematically, each region is investigated from the Neolithic to the present day and, through 'Intensive Survey Zones' - selected to give a representative range of the physical and cultural terrain - many notable new discoveries are made. These include the pattern of Bronze Age Settlement in the Plains, Archaic rural sanctuaries and cemeteries, the scope of Late Roman copper-mining and isolated Medieval mountain settlements. The TAESP Landscape provides a fully integrated and data-rich analysis of the material from a wide range of contrasting archaeological perspectives. Taken together, these wide-ranging and interdisciplinary perspectives give a nuanced and sensitive approach to a strikingly multi-faceted landscape.